How Is Ethical Leadership Linked to Subordinate Taking Charge? A Moderated Mediation Model of Social Exchange and Power Distance - Wang, Qiao; Zhou, Xiaohu; Bao, Jiani; Zhang, Xueyan; Ju, Wei (Frontiers in Psychology, 2020)
Extant literature has suggested that leadership styles have a significant impact on subordinate taking charge. However, the effect of ethical leadership on subordinate taking charge has still insufficiently explored. Drawing on social exchange theory, we developed a moderated mediation model in which social exchange was theorized as a mediating mechanism underlining why subordinates feel motivated to take charge with the supervision of ethical leadership. Moreover, power distance was supposed to be a relevant boundary condition to moderate such a relationship. 239 independent leader–subordinate dyads in China has been used to test the model. Results showed that subordinates’ social exchange mediates the relationship between ethical leadership and subordinate taking charge, and such a relationship was found to be stronger among subordinates who had lower levels of power distance rather than higher levels. Theoretical and practical implications concerning to enhance subordinate taking charge in organizations where ethical leaderships exist are discussed.